2019
DOI: 10.3390/ma12101638
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Impact Toughness of Local-Dry Keyhole Tungsten Inert Gas Welded Joints

Abstract: In this paper, the microstructure and impact toughness of a S32101 duplex stainless steel underwater local-dry keyhole tungsten inert gas welded joint were studied. The impact toughness value of the underwater weld metal reached 78% of the onshore weld metal, which is in accordance with the underwater welding standards. The proportion of austenite in the underwater weld metal was 0.9% lower than that of the onshore weld metal. The proportion of the Σ3 coincidence site lattice boundaries and random phase bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…Keyhole tungsten inert gas (K-TIG) welding is a kind of high-energy beam welding method. It can be welded in a single-pass welding and formed on both sides without filling the welding material [ 10 , 11 , 12 , 13 , 14 ]. In this paper, different welding speeds were applied to analyze the influence of cooling rate on morphology, mechanical properties, and microstructure of the 2205 DSS welds.…”
Section: Introductionmentioning
confidence: 99%
“…Keyhole tungsten inert gas (K-TIG) welding is a kind of high-energy beam welding method. It can be welded in a single-pass welding and formed on both sides without filling the welding material [ 10 , 11 , 12 , 13 , 14 ]. In this paper, different welding speeds were applied to analyze the influence of cooling rate on morphology, mechanical properties, and microstructure of the 2205 DSS welds.…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al studied the welded joints of duplex stainless steel by ULDCW. The result showed that the impact toughness met the requirements of UW criterions and the ratio of austenite reduced in the underwater weld metals compared with the in-air weld metals [16]. Zhang et al studied the influence of shielding conditions and optical signals on the quality of weld metals during ULBW, respectively [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been demonstrated that K-TIG has the potential to increase the productivity while maintaining the mechanical properties at a level similar to the joints produced by conventional TIG welding. Recently, it was reported by Cui et al [11] that K-TIG can even be used in underwater condition and can produce a duplex stainless-steel weld that meets underwater welding standards. In addition, because of the fact that the material properties of some welded joints produced by K-TIG are not satisfactory, several optimisation technologies have been introduced into the K-TIG welding process.…”
Section: Of 15mentioning
confidence: 99%